Public perception on lesbian, gay, bisexual and transsexual instafamous credibility in promoting products on Instagram / Jeffica D. Tudol, Ahlam Abdul Aziz and Shazleen Mohamed - D. Tudol, Jeffica; Abdul Aziz, Ahlam; Mohamed, Shazleen (Universiti Teknologi MARA, 2022)
The increased use of social media among consumers is giving marketers more attention to promoting their products by social media channels. On Instagram, individuals who have many followers are called “Instafamous” and in Malaysia, one of the groups that have many followers on Instagram is the LGBT community. For the marketer, LGBT Instafamous can be used as an opportunity for the branding of their brands or products because they need a marketing that can be carried out in a short time without spend too many expenses. Therefore, the main purpose of this research paper is to understand public perception about the credibility of LGBT Instafamous in promoting products on Instagram. The objectives of the research are (i) to identify level of public perception towards LGBT instafamous on Instagram, (ii) to identify level of credibility of LGBT instafamous in promoting products and (iii) to determine the relationship between public perception and credibility of LGBT instafamous in promoting products on Instagram. Quantitative design has been applied to this research with purposive sampling as a research methodology. To conduct this research, an online survey consisted 30 questions with a 5-point Likert Scale Response was distributed only to Instagram user between 28-54 years old. From the result, we can see that the level of perception is in a moderate level but high in a level of credibility and there is a strong relationship between the public perception and the credibility of the LGBT Instafamous in reviewing brand or products on Instagram.